Municipal contraceptive services, socioeconomic status and teenage pregnancy in Finland: a longitudinal study - Oskari Heikinheimo; Mika Gissler; Eerika Jalanko; Frida Gyllenberg; Nikolas Krstic (BMJ Open)
Objectives Declining teenage pregnancy rates have been linked to improved access to youth-friendly contraceptive services, but information on the combined association of these services and socioeconomic factors with teenage pregnancy is lacking.Design and setting This retrospective longitudinal register-based study covers the annual teenage childbirth and induced abortion rates in the 100 largest municipalities in Finland in 2000–2018. We investigated the combined association of regional, socioeconomic (ie, education level and need for social assistance) and adolescent contraceptive service variables (ie, free-of-charge contraception, an adolescent-only clinic and availability of over-the-counter emergency contraception (OTC EC)) with teenage childbirth and induced abortion rates at the municipality level by using Poisson mixed-effects model.Primary outcome measures Annual teenage childbirth and induced abortion rates as numbers per 1000 teenage girls aged 15–19 years old in the 100 largest municipalities in Finland from 2000 to 2018.Results The following variables were significantly associated with both lower teenage childbirth and induced abortion rates when adjusted for all the other variables used in the model: providing free-of-charge contraception (rate ratio (RR) 0.82 (95% CI 0.73 to 0.92) and RR 0.87 (95% CI 0.79 to 0.96), respectively), availability of OTC EC without age limit (RR 0.70 (95% CI 0.67 to 0.75) and RR 0.74 (95% CI 0.71 to 0.78), respectively), and high education level of the municipality (RR 0.94 (95% CI 0.94 to 0.95) and RR 0.94 (95% CI 0.93 to 0.94), respectively).Conclusion Providing free-of-charge contraception and availability of OTC EC without age limit are associated with lower teenage pregnancy rates. These services combined with proper counselling are thus important contents of youth-friendly contraceptive services that should be provided equally for all teenagers in order to further reduce teenage pregnancy rates.